Cable-Driven Parallel Robots Proceedings of the 4th International Conference on Cable-Driven Parallel Robots - Pott, Andreas; Bruckmann, Tobias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume gathers the latest advances, innovations, and applications in the field of cable robots, as presented by leading international researchers and engineers at the 4th International Conference on Cable-Driven Parallel Robots (CableCon 2019), held in Krakow, Poland on June 30-July 4, 2019, as part of the 5th IFToMM World Congress. It covers the theory and applications of cable-driven parallel robots, including their classification, kinematics and singularity analysis, workspace, statics and dynamics, cable modeling and technologies, control and calibration, design methodologies, hardware development, experimental evaluation and prototypes, as well as application reports and new application concepts. The contributions, which were selected through a rigorous international peer-review process, share exciting ideas that will spur novel research directions and foster new multidisciplinary collaborations.
Keywords: Control engineering; Robotics; Automation; Mechatronics; Machinery; Control, Robotics, Automation; Mechatronics; Machinery and Machine Elements